2012
DOI: 10.1128/jb.00076-12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iacP Mutation on Flagellar Phase Variation in Salmonella enterica Serovar Typhimurium Strain UK-1

Abstract: c Flagella are surface appendages that are important for bacterial motility and invasion of host cells. Two flagellin subunits in Salmonella enterica serovar Typhimurium, FliC and FljB, are alternatively expressed by a site-specific DNA inversion mechanism called flagellar phase variation. Although this inversion mechanism is understood at the molecular level, the key factor controlling the expression of the two flagellin subunits has not been determined. In this study, we found that a putative acyl carrier pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 36 publications
3
9
0
Order By: Relevance
“…Yang et al observed that the flagellar overexpression attenuates Salmonella virulence and elicits an elevated immune response via flagellin adjuvant, thereby conferring robust protection against Salmonellosis [8]. We previously found that the expression level of the fljB gene was higher in the iacP mutant strain grown under SPI1-inducing conditions, although the expression of the fliC gene was independent of IacP [7]. As expected, the iacP mutant strain produced more flagella than the wild-type strain.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Yang et al observed that the flagellar overexpression attenuates Salmonella virulence and elicits an elevated immune response via flagellin adjuvant, thereby conferring robust protection against Salmonellosis [8]. We previously found that the expression level of the fljB gene was higher in the iacP mutant strain grown under SPI1-inducing conditions, although the expression of the fliC gene was independent of IacP [7]. As expected, the iacP mutant strain produced more flagella than the wild-type strain.…”
Section: Introductionsupporting
confidence: 55%
“…Bacterial flagella are appendages on the cell surface that are required for the motility and chemotaxis of bacterial pathogens and for epithelial cell invasion as a virulence factor [6,7]. Flagellins, a key component of the bacterial flagella, are recognized as PAMPs in host cells, through binding with TLR5 and NLRC4.…”
Section: Introductionmentioning
confidence: 99%
“…The use of an essential function as the one performed by AcpS may ensure that the bacterial pathogen maintains the capacity to mature the virulence-associated protein IacP. As mentioned earlier, IacP has been proposed to promote the secretion of the protein effectors SopA, SopB, and SopD (16) and to influence the Hin DNA invertase-mediated flagellar phase variation (17). However, in light of what is known about the mode of action of ACPs, it is unclear at this stage how IacP would regulate these events.…”
Section: Resultsmentioning
confidence: 99%
“…The proposed explanation for this phenotype was that IacP might promote secretion and translocation of specific protein effectors: SopA, SopB, and SopD (16). It has also been reported that IacP might be involved in the regulation of flagellin expression (17). In the two studies, the conserved serine 38 residue was required for the observed roles of IacP, suggesting that maturation was occurring on IacP and was necessary for its activity.…”
mentioning
confidence: 87%
“…Confirmation of flagellin phase switching was performed at both the protein and DNA level, as described previously (34)(35)(36). The primers used to assay genomic DNA for flagellin phase are indicated in Table S3 in the supplemental material.…”
mentioning
confidence: 99%